Analisis Ergonomi Operator Picker Warehouse pada PT. XYZ dengan Metode RULA (Rapid Upper Limb Assessment) - Jakarsodik, Ghani; Halim, Hafidz Akbar; Hidayat, Ade Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. XYZ is engaged in the manufacturing industry. In the work process, especially in the warehouse section with a fairly fast intensity in supplying production, a proper and safe work process is required. In the work process in the warehouse, there are problems conveyed by the operator regarding the pain felt in the arms and waist during the work process. The pain experienced includes Musculoskeletal Disorders (MSDs), which is pain felt by the muscles, this study aims to determine the level of risk of body posture during work using the Rapid Upper Lamb Assessment method, what factors cause this to happen. The results of the analysis using RULA and improvements, obtained unsafe work postures due to inappropriate tools and causing pain to the operator, with improvements to the work tools used, the pain experienced by workers subsided and disappeared during the work process